Conversion Disorder - Yacov Rofé; Yochay Rofé (Europe's Journal of Psychology, 2013)
Conversion disorder remains a mystery that has only become more complicated with the decline of the scientific status of psychoanalysis (e.g., Piper, Lillevik, & Kritzer, 2008; Rofé, 2008) and recent neurological findings suggest that this behavior is controlled by biological mechanisms (van Beilen, Vogt, & Leenders, 2010). Moreover, existing theories have difficulty explaining the efficacy of various interventions, such as psychoanalysis, behavior therapy, drug therapy and religious therapy. This article reviews research and clinical evidence pertaining to both the development and treatment of conversion disorder and shows that this seemingly incompatible evidence can be integrated within a new theory, the Rational-Choice Theory of Neurosis (RCTN; Rofé, 2010). Despite the striking differences, RCTN continues Freud's framework of thinking as it employs a new concept of repression and replaces the unconscious with self-deception. Moreover, it incorporates Freud's idea, implicitly expressed in his theory, that neurotic disorders are, in fact, rational behaviors.